Differential Changes in Striatal Projection Neurons in R6/2 Transgenic Mice for Huntington's Disease - Z. Sun (Neurobiology of Disease, 2002)
In early adult-onset Huntington's disease (HD), enkephalinergic striatopallidal projection neurons show preferential loss, reduced preproenkephalin (PPE) expression in surviving striatopallidal neurons, and loss of fibers in their projection target area. We examined PPE and PPT (preprotachykinin) gene expression in striatal projection neurons and in striatal projection fibers immunoreactive for the PPE product enkephalin (ENK) and the PPT product substance P (SP) in a transgenic HD model, the R6/2 mouse, to see if changes occur in these neuron types similar to those seen in early adult-onset HD. The results show that PPE mRNA level, the number of striatal neurons expressing PPE, and the staining intensity of fibers immunoreactive for ENK in the pallidum were all decreased. By contrast, the SP-containing striatal projection systems to the pallidum and substantia nigra were relatively normal in R6/2 mice. The selective reduction in striatal PPE in R6/2 mice is reminiscent of adult-onset HD, but the preservation of the striatonigral projection system is not. Thus, R6/2 mice do not strictly mimic adult-onset HD in their striatal pathology.